Assessing the Impact of Faculty Developer Initiatives in Higher Education: Testing and Adapting Methodological Tools - Daele, Amaury; Ricciardi Joos, Paola; Schaub, Mallory; Barras, Hervé; Lambert, Marie; Rochat, Jean-Moïse; Stainier, Nadine (Swiss Journal of Educational Research, 2018)
This paper investigates the impact of faculty developers’ actions in Higher Education. We focus on the methodology of the evaluation of our actions reach. Firstly we identify steps, criteria and useful indicators to lead such evaluation, on the basis of existing models. We then test our methodology through a self- and peer-evaluation approach of faculty developers’ representative set of actions. The outcomes of this evaluation have then been discussed by experts at a faculty developers’ international meeting. This meeting has been used as a framework to analyse and adapt useful tools to evaluate our actions reach. This reflection highlighted the complexity and the issues of the evaluation of our missions. As result, the paper proposes full usable evaluation tools.